الضمانات الحديثة لتنفيذ الأحكام القضائية – دراسة مقارنة - محمد شكري قواسمية; فاطمة الزهرة كلاعي (My University, 2025)
Abstract Modern guarantees for the enforcement of judicial rulings represent one of the most important legal developments aimed at enhancing the effectiveness of the judiciary and protecting individual rights, especially in the face of administrative bodies’ refusal to implement judicial decisions. These guarantees reflect a fundamental shift from relying on traditional, insufficient means to stricter mechanisms such as binding judicial orders and imposing punitive fines, which contribute to achieving timely justice and strengthening the principle of the rule of law. The study highlights the importance of comparing different legal systems, particularly the Egyptian and French systems, to benefit from successful experiences and develop national legislation. These guarantees also face multiple challenges that require in-depth study and critical analysis to provide effective recommendations ensuring the actual and effective enforcement of judicial rulings. Given these circumstances, the study of modern guarantees gains great importance in enhancing the role of administrative judiciary, achieving a balance of powers, and protecting rights. ........................ ملخص: تعد الضمانات الحديثة لتنفيذ الأحكام القضائية من أهم التطو ارت القانونية التي تهدف إلى تعزيز فعالية القضاء وحماية حقوق الأفراد، خاصة في مواجهة امتناع الجهات الإدارية عن تنفيذ الأحكتم القضائية. تعكس هذه الضمانات تحولا جوهريا من الاعتماد على الوسائل التقليدية غير الكافية إلى آليات أكثر صرامة مثل الأوامر القضائية الملزمة وفرض الغرامات التهديدية، مما يسهم في تحقيق العدالة الناجزة وتعزيز مبدأ سيادة القانون. وتبرز الدراسة أهمية المقارنة بين الأنظمة القانونية المختلفة، لاسيما النظام المصري والفرنسي، للإستفادة من التجارب الناجحة وتطوير التشريعات الوطنية. كما تواجه هذه الضمانات تحديات متعددة تتطلب دراسة معمقة وتحليل نقدي لتقديم توصيات فعالة تضمن تنفيذ الأحكام القضائية بشكل فعلي وفعال. في ظل هذه المعطيات، تكتسب دراسة الضمانات الحديثة أهمية بالغة في تعزيز دور القضاء الإداري وتحقيق التوازن بين السلطات وحماية الحقوق. .............................. Résumé : Les garanties modernes d'exécution des décisions judiciaires constituent l'un des développements juridiques les plus importants visant à renforcer l'efficacité du système judiciaire et à protéger les droits des individus, en particulier face au refus des autorités administratives d'exécuter les décisions judiciaires. Ces garanties reflètent un changement fondamental qui consiste à passer de moyens traditionnels inadéquats à des mécanismes plus rigoureux tels que des ordonnances judiciaires contraignantes et l'imposition d'amendes, ce qui contribue à une justice rapide et au renforcement du principe de l'État de droit. L'étude souligne l'importance de comparer différents systèmes juridiques, en particulier les systèmes égyptien et français, afin de tirer parti des expériences réussies et de développer une législation nationale. Ces garanties sont confrontées à de multiples défis qui nécessitent une étude approfondie et une analyse critique afin de fournir des recommandations efficaces pour assurer la mise en œuvre effective et efficace des décisions judiciaires. À la lumière de ces faits, l'étude des garanties modernes est d'une grande importance pour renforcer le rôle de la justice administrative, atteindre un équilibre entre les autorités et protéger les droits.
Keywords: Keywords : enforcement of judicial rulings; modern guarantees; administrative judiciary; rule of law; judicial orders; punitive fines; comparative study.; كلمات مفتاحية: تنفيذ الأحكام القضائية، الضمانات الحديثة، القضاء الإداري، مبدأ سيادة القانون، الأوامر القضائية، الغرامات التهديدية، الدراسة المقارنة.; Mots-clés : Exécution des jugements judiciaires; garanties modernes; pouvoir judiciaire administratif; État de droit; ordonnances judiciaires; menaces d'amendes; étude comparative.